Pescadores artesanais na praia de Copacabana: histórias e memórias - tradições e temporalidades - Bernardo, Luzimar Soares (2019)
In the period between 1919 and 1923, the Brazilian Navy instituted more than 800 fishermen colonies all along the Brazilian coast. According to what was then issued by the one who headed the mission of creating these colonies, Admiral Frederico Villar, the government was concerned about these workers that was, in their great majority, illiterate who were working in a very precarious conditions. With a regulating plan to nationalize the fishing, the Colonies were established. Those who did not accepted to nationalize have been banned from fishing legally. To those who met the new working model, has been promised, among other things, school for the workers and their families, medical and dental assistance, as well as improvement of the working conditions and fishery resources donation to improve their living conditions. Therefore, this research intends to understand the importance of fishing officialization for the workers, its evolution over the years, and how the State bears, nowadays, the subjects who are part of this activity. In particular, those who are allocated at Posto Seis (Watchtower Six) in Copacabana, that they are an integral part of the Z-13 Colony